Salt Marketing Strategy Design Using The SWOT - STP Method - Lukman Hanif; Widyastuti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Marketing strategy is an important factor to achieve the success of marketing a product. Kugar Sari Laut is a salt business group that produces salt consumption and salt innovation. During the COVID-19 pandemic, Kugar Sari Laut sales turnover decreased by 50%. Therefore, for the company's sustainability, it was necessary to design a better marketing strategy. This study presents a marketing strategy design using combination SWOT and STP methods. SWOT (Strengths, Weakness, Opportunities, and Threats) method was used to identify marketing systems in Kugar Sari Laut. The salt quality identification survey was conducted to 400 respondents of salt users in Kebumen Regency. Observation of internal and external factors was carried out to the manager of Kugar Sari Laut. SWOT analysis results in four internal criteria (material, method, machine, person) and two external criteria (needs, competitors). Based on it, marketing strategy was designed using the STP method (Segmenting, Targeting, and Positioning). The segmentation aspect consists of two criteria: demographic and geographic. There were six criteria of targeting: method, people, demographic, geographic and trial duration. salt packaging variations are applied to the positioning aspect. The next process was testing new marketing strategy for two months. Wilcoxon test was used to validate the results of this process. The validation shows that there was a positive influence on the implementation of new marketing strategy.